Kajian Evaluatif Perselisihan Hasil Pemilihan (PHP) Kepala Daerah Serentak Tahun 2020 Di Provinsi Kalimantan Selatan - Muhammad Syahrial Fitri; hanafi hanafi (Al-Adl : Jurnal Hukum, 2023)
This research will discuss, First, the factors that are the causes of the Election Result Disputes (PHP) for the 2020 Regional Heads of the South Kalimantan Province at the Constitutional Court and Second, the consequences that arise in the Implementation of the Decisions on the Election Result Dispute (PHP) for the 2020 Regional Heads of the Province Simultaneously South Kalimantan at the Constitutional Court. This research was conducted using the Normative Juridical approach, which examines statutory regulations and other literature related to regional head election results in disputes (PHP) at the Constitutional Court. The review of laws and regulations and library materials is also used as material for conducting discussions and finding solutions to problems. This study examines the causes of disputes over election results up to the implementation of decisions. It will identify existing problems in the form of solutions under the provisions of the election law and regional head elections in Indonesia. The results of this study show that the Election Results Dispute (PHP) for Regional Heads of South Kalimantan Province Simultaneously in 2020 at the Constitutional Court does not only originate from the Election of the Governor and Deputy Governor of South Kalimantan but there also from PHP Regents and Deputy Regents of Banjar Regency, Kota Baru Regency and Wali City and Deputy Mayor of Banjarmasin City, totalling seven decisions, two decisions for PHP Governor and Deputy Governor, 3 Decisions of Regent and Deputy Regent (Banjar and Kota Baru), 2 Decisions of Mayor and Deputy Mayor (Banjarmasin). The factors causing the Election Result Disputes (PHP) for Regional Heads of South Kalimantan Province Simultaneously in 2020 at the Constitutional Court consist of 2 factors. First, regulatory factors, namely the threshold for disputes over election results. % at polling places, PPK opened mailboxes, and there was vote inflation and fraud in the voting and vote-counting process. Furthermore, there are two aspects of the legal consequences arising from the implementation of the Constitutional Court decision. First, the implementation of the re-voting (PSU) and Second, the determination of the elected regional head candidates.